Comparing the Effect of DOAC-Stop® and DOAC-Remove® on Apixaban, Rivaroxaban and Dabigatran Prior to Thrombophilia and Lupus Testing - Noor-; Andrew Ward; Beth Erskine (Frontiers Media S.A., 2024)
BackgroundDirect oral anticoagulants (DOACs) interfere with coagulation assays potentially leading to inaccurate results. This study determined the effectiveness of DOAC-stop® and DOAC-remove® in overcoming DOAC interference. It aimed to investigate the extent to which apixaban, rivaroxaban, and dabigatran had an effect on thrombophilia and lupus tests using normal plasma, as well as whether DOACs interfere with true-positive results by testing abnormal controls.MethodsApixaban (0.03 mg/mL), rivaroxaban (0.01 mg/mL), and dabigatran (0.019 mg/mL) stock solutions were made and added to the normal pool at three different concentrations (200, 400 and 600 ng/mL) and to the abnormal controls at a single concentration. These samples and untreated DOAC controls were tested before and after adding either DOAC-stop® or DOAC-remove®. The measured parameters included protein C, protein S, antithrombin III (ATIII), DRVVS, DRVVC, PTT-LA and DOAC concentration. The normal pool spiked with DOAC was repeated seven times for each DOAC at each concentration level and the abnormal controls spiked with DOAC were repeated four times at a single concentration level for each DOAC.ResultsIn the normal pool, dabigatran and rivaroxaban affected all lupus anticoagulant tests, whereas apixaban only affected DRVVS and DRVVC. While dabigatran led to false-positive protein S deficiency and falsely elevated ATIII. Both DOAC-stop® and DOAC-remove® brought the thrombophilia results and all falsely elevated lupus anticoagulant results back within the normal range for apixaban and rivaroxaban. For dabigatran all the affected lupus anticoagulant tests remained abnormal following DOAC-remove®, unlike DOAC-stop® treatment, where only DRVVS and DRVVC at 600 ng/mL remained abnormal. In abnormal controls, all DOACs falsely elevated the lupus anticoagulant tests, whereas dabigatran caused false negative ATIII results, that were corrected (remained abnormal) with DOAC-stop® and DOAC-remove®. DOAC-stop® showed a greater reduction in lupus anticoagulant results than DOAC-remove®, causing a false-negative DRVVT ratio for rivaroxaban.ConclusionDOAC-stop® is more effective than DOAC-remove® in removing all DOACs below the reference range, whereas DOAC-remove® failed to remove dabigatran.